The Expanding Role of Sonography in the Clinical Practice of Modern Obstetrics and Gynecology: A Clinical Perspective. (May 2023) - Levine, Elliot M.; Fernandez, Carlos M.
A list of gynecologic diagnoses is provided, which shows the use of sonography in significantly assisting the practice of modern clinical gynecology. The clinical value of this technology to assist in formulating diagnoses for the presenting patients is discussed. Sonography has become a necessary tool for today's practice of gynecology, and women's health, in general.